A Study of the Relationship between Type of Organizational Structure of University and Departmental Social Capital with Students\\\' Academic Satisfaction at Shiraz University - jafar torkzadeh; maasuomeh mohtaram (جامعه شناسی کاربردی, 2014)
Introduction The University's mission, in addition to teaching, conducting research and giving service to the academic community, is to help improve the all-round develop‌ment of students (Astin, 1993). Collecting information on students’ academic satisfaction, which is mentioned to be as an outcome (Austin, 1993 b; Sanders and Chan, 1996) or a designed tool for improving the quality of students' expe‌riences (Aldridge and Rowley, 1998) is one of the proceedings that assist the universities to perform this mission well. Providing Students' satisfaction as the most important stakeholders of the university is subject to providing an appropriate context, including an extensive network of positive relationships and partnerships between educational stakeholders. This can be called social capital. Social capital is a set of existing norms, networks and social trust at the university system, which leads to the satisfaction of students with different aspects of education by facilitating cooperation between departments and reducing transaction costs. However, realization of students’ expectations and development of social capital within the organization, particularly universities, are influenced by a number of factors, among which organizational hindering and enabling structures are the most important ones. If the organizational structure is hindering, not only will it destroy the social capital, but it result in distrust among members toward one another and reduction of their satisfaction as well. Thus, the concept of organizational structure and social capital and the presence of a kind of co- finalization between the two variables, a climate coupled with trust, cooperation, sincerity, and responsibility all provide a proper context in order to obtain the academic satisfaction of students. In this study, we attempted to investigate the relationship between these three variables in terms of a structural equation model. The following assumptions were thus made: 1) There is a significant relationship between the type of organizational structure and students’ academic satisfaction. 2) There is a significant relationship between departments’ social capital and students’ academic satisfaction. 3) There is a significant relationship between the type of organizational structure and departments’ social capital with the academic satisfaction of students.